Phagocytosis of leprosy bacilli is mediated by complement receptors CR1 and CR3 on human monocytes and complement component C3 in serum. - Schlesinger, L S (1990)
Mycobacterium leprae, an obligate intracellular pathogen, invades and multiplies within host mononuclear phagocytes. To understand M. leprae invasion better, we have investigated the role of phagocyte receptors and bacterium-bound ligands in phagocytosis of M. leprae by human monocytes. Complement receptors CR1 and CR3 mediate adherence and phagocytosis of M. leprae in nonimmune serum. Two MAbs used in combination against CR3 inhibit adherence by up to 90 +/- 3%. Two MAbs used in combination against CR1 and CR3 inhibit adherence by up to 70 +/- 1%. Single MAbs against CR1 or CR3 consistently inhibit adherence by 38-55%. In contrast, MAbs against other monocyte surface molecules, alone or in combination, do not significantly influence adherence. As studied by electron microscopy, 100% of monocyte-associated M. leprae are ingested in the presence of nonimmune serum and MAbs against CR3 markedly inhibit ingestion. Complement receptors CR1 and CR3 also mediate the low level of adherence observed in the absence of serum. Serum complement component C3 serves as a ligand on the bacterial surface in monocyte phagocytosis of M. leprae. Adherence of M. leprae to monocytes is enhanced by preopsonization (3.1 +/- 1.1-fold increase) and is markedly reduced in less than 0.5% fresh serum (66 +/- 7% reduction) or heat-inactivated serum (68 +/- 3% reduction). Adherence is also markedly reduced in C3- or factor B-depleted serum; repletion with purified C3 or factor B increases adherence 4.3 +/- 0.8- and 2.6 +/- 0.2-fold, respectively. C3 is fixed to M. leprae by the alternative pathway of complement activation, as determined by a whole bacterial cell ELISA. By electron microscopy, monocytes ingest M. leprae by conventional phagocytosis. This study demonstrates that (a) human monocyte complement receptors CR1 and CR3 mediate phagocytosis of M. leprae; (b) complement component C3 on the bacterial surface serves as a ligand for complement receptors; (c) complement component C3 binds to M. leprae by the alternative pathway of complement activation; and (d) monocytes phagocytize M. leprae by conventional phagocytosis.